Outward particle transport by coherent mode in the H-mode pedestal in the Experimental Advanced Superconducting Tokamak (EAST). (5th May 2017) - Zhang, T; Han, X; Gao, X; Liu, H Q; Shi, T H; Liu, J B; Liu, Y; Kong, D F; Liu, Z X; Qu, H; Xiang, H M; Geng, K N; et al.
Abstract: A coherent mode (CM) in the edge pedestal region has been observed on different fluctuation quantities, including density fluctuation, electron temperature fluctuation and magnetic fluctuation in H mode plasma on the Experimental Advanced Superconducting Tokamak (EAST) tokamak. Measurements at different poloidal positions show that the local poloidal wavenumber is smallest at the outboard midplane and will increase with poloidal angle. This poloidal asymmetry is consistent with the flute-like assumption (i.e. k//  ∼ 0) from which the toroidal mode number of the mode has been estimated as between 12 and 17. It was further found that the density fluctuation amplitude of the CM also demonstrated poloidal asymmetry. The appearance of a CM can clearly decrease or even stop the increase in the edge density, while the disappearance of a CM will lead to an increase in the pedestal density and density gradient. Statistical analysis showed there was a trend that as the CM mode amplitude increased, the rate of increase of the edge density decreased and the particle flux (Γdiv ) onto the divertor plate increased. The CM sometimes showed burst behavior, and these bursts led bursts on Γdiv with a time of about 230 μ s, which is close to the time for particle flow from the outer midplane to the divertor targets along the scrape-off layer magnetic field line. This evidence showed that the CM had an effect on the outward transport of particles.